2020
DOI: 10.1177/1179173x20938773
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco Use Among College Students Across Various Disciplines in Kerala, India

Abstract: Background: Tobacco use is a major public health concern in India. Its use in young people is linked to increased severity, longer duration, and reduced efforts to seek treatment for tobacco use. A significant proportion of young people are enrolled in colleges, and early prevention during this period has better effectiveness. There is preliminary evidence that prevalence may vary across courses even among students of the same sociocultural background. Hence, we compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 14 publications
0
10
1
Order By: Relevance
“…Alcohol consumption was associated with tobacco smoking in a study by Menon et al [ 45 ] conducted in India on 58 colleges (medical included), which is not consistent with our results, that did not indicate that alcohol consumption was a statistically significant predictor of the students smoking status. The same study indicates that there was consistent evidence that drinking alcohol increased the risk of smoking tobacco [ 45 ]. A study by Nasui et al [ 36 ], conducted in Romania on medical students, provides evidence that alcohol consumption was a positive predictor of smoking.…”
Section: Discussioncontrasting
confidence: 99%
“…Alcohol consumption was associated with tobacco smoking in a study by Menon et al [ 45 ] conducted in India on 58 colleges (medical included), which is not consistent with our results, that did not indicate that alcohol consumption was a statistically significant predictor of the students smoking status. The same study indicates that there was consistent evidence that drinking alcohol increased the risk of smoking tobacco [ 45 ]. A study by Nasui et al [ 36 ], conducted in Romania on medical students, provides evidence that alcohol consumption was a positive predictor of smoking.…”
Section: Discussioncontrasting
confidence: 99%
“…The tobacco use in our study population is also much higher than those of 18-24 years old college girls in Mangalore; smoking tobacco, 2.1%, and SLT use, 3.3% (Jodalli and Panchmal, 2019). Likewise, the reported prevalence of any form of tobacco use in college girls from medical, nursing, engineering, arts and science faculties in Ernakulum, Kerala (Menon et al, 2020) being 1.0%, 0.5%, 1.2%, and 1.1%, respectively, are far lower than those found by us. The girls in our study also showed much higher tobacco prevalence than in female students from 25 Universities from low-and middle-income countries reported by Pelzer and Pengpid (2014).…”
Section: Discussionmentioning
confidence: 50%
“…Low- and middle-income countries (LMICs) are home to more than 80% of the tobacco users of the world, and thus contribute significantly to tobacco-related mortality and morbidity [ 8 ]. Tobacco use is projected to kill one billion in the 21st century and 80% of these deaths will be from LMICs [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The widespread use of tobacco in the developing world is attributed to its low price, variations in form, lack of awareness on harmful effects, unregulated aggressive marketing by the tobacco industry and lack of public health policies advocating for its complete ban. India is home to approximately 266.8 million tobacco users and is the second largest consumer of tobacco in the world [ 8 , 10 ]. India’s tobacco landscape is more complex due to the extensive production facilities and use of many smokeless forms of tobacco.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation